Implementation of IoT-Based Smart Agro Culture to Empower and Strengthen Onion MSME Entrepreneurship in Pengklik Village, Madurejo Prambanan - Pranoto, Aji; Wahyudi, Idam; Sholeh, Muhammad; Gde Badrawada, I Gusti (University of Muhammadiyah Malang, 2026)
Pengklik Village in Madurejo Village, Kapanewon Prambanan, has great shallot farming potential but faces limitations in productivity and product added value. This study aims to analyse the application of Smart Agro Culture based on the Internet of Things (IoT) in increasing harvest productivity and strengthening onion MSME entrepreneurship. The research method uses a descriptive quantitative approach with comparative analysis of crop yields before and after the application of IoT technology. Data was obtained from field observations, MSME questionnaires, and production records on an area of 660 m² of onions. The results show a significant increase in harvest productivity, from 173 kg in 2023 to 2710 kg in 2024, after using IoT-based automatic sprinkle systems. In addition, the application of IoT supports the process of standardising MSME products through digital processing, packaging, and marketing. These findings confirm that IoT-based Smart Agro Culture not only increases productivity but also strengthens the competitiveness of local MSME entrepreneurship.